Occupational Performance Priorities of Children With Cerebral Palsy From the Parents' Perspective - Nasrin Jalili; Zahra Nasr; Rouhollah Zare; Mahsa Sattari; Ali Hosseini (University of Social Welfare and Rehabilitation Sciences, 2019)
Objective Cerebral Palsy (CP) is a group of non-progressive disorders in a developing brain that results in motor problems and other limitations in daily living activities. The presence of motor functions in these children reduces their participation in daily activities. This is one of the important aspects of the child's health and development, especially the child's physical and psychological development. Participation in social activities promotes life satisfaction. Besides, family has a prominent role in identifying and supplying the child's needs. In other words, family plays an essential role in ensuring the health and well-being of their children. Thus, provisions of growth-related health services has now changed from a child-cantered model into a family-cantered model. As a result, it is very important to understand the parents' priorities about participation of their children in the daily activities and providing appropriate client-center services. Materials & Methods In this descriptive-analytic study, 78 children and teenagers with CP aged 3-18 years without psychiatric problems and their parents from Yazd City, Iran had participated. The samples were selected by convenience sampling method, from clients of private and public rehabilitation centers in Yazd Province. In this regard, one state and two private centers were randomly selected and the study samples were selected from the clients referred to the centers. Parents' priorities for participation of their children in activities of daily living were found through semi-structured interviews. In these interviews, we used Canadian occupational performance measure to evaluate the child's level of occupational performance and parents' satisfaction in the three areas of self-care, productiveness, leisure from the parents' perspective. In addition, the level of gross motor performance was evaluated based on the Gross Motor Function Classification System (GMFCS) at five levels. In the Iranian society, the validity of Canadian occupational performance measure for each of three areas of occupational performance has been reported to be between 9.75 and 3.75 and the reliability level for the three domains reported above 0.78. The statistical analysis of data was performed in SPSS V. 16. Descriptive statistics and odds ratio were used for analyzing the data. Results the children' Mean±SD age was 8.12±4.22 years. The first priority reported by the parents was self-care. Mobility was known as the second important priority in everyday life for children. The results obtained from the statistical analysis showed no significant relationship between age and different motor levels (P≥0.05). Conclusion Parents reported functional priorities in similar performance aspects by all age groups and GMFCS levels in Cerebral Palsy children. The first priority was related to self-care. This reflects the desire of the parents to children' doing self-care activities, which not only reduces care pressure, but also leads to promotion in social participation and independence in individual life. The next priority was mobility and the reason can be attributed to the fact that children with CP need mobility to manage their daily life activities.